Modulating Epitaxial Atomic Structure of Antimonene through Interface Design. Issue 29 (3rd June 2019) - Niu, Tianchao; Zhou, Wenhan; Zhou, Dechun; Hu, Xuemin; Zhang, Shengli; Zhang, Kan; Zhou, Miao; Fuchs, Harald; Zeng, Haibo
Abstract: Antimonene, a new semiconductor with fundamental bandgap and desirable stability, has been experimentally realized recently. However, epitaxial growth of wafer‐scale single‐crystalline monolayer antimonene preserving its buckled configuration remains a daunting challenge. Here, Cu(111) and Cu(110) are chosen as the substrates to fabricate high‐quality, single‐crystalline antimonene via molecular beam epitaxy (MBE). Surface alloys form spontaneously after the deposition and postannealing of Sb on two substrates that show threefold and twofold symmetry with different lattice constants. Increasing the coverage leads to the epitaxial growth of two atomic types of antimonene, both exhibiting a hexagonal lattice but with significant difference in lattice constants, which are observed by scanning tunneling microscopy. Scanning tunneling spectroscopy measurements reveal the strain‐induced tunable bandgap, in agreement with the first‐principles calculations. The results show that epitaxial growth of antimonene on different substrates allow the electronic properties of these films to be tuned by substrate‐induced strain and stress. Abstract : High‐quality antimonene with different lattice constants is fabricated by molecular beam epitaxy on alloyed Cu(111) and Cu(110) modulated by the interfacial interaction. A strain‐induced tunable bandgap is distinctly revealed by scanning tunneling spectroscopy complemented by theoretical calculations. A method by using alloyed surfaces with different symmetries, which allows the electronic properties of 2D materials to be tuned by introducing strain is provided.